Serpentine seamounts of Pacific fore-arcs drilled by the Ocean Drilling Program: Dr. Hess would be pleased - Keen, M.; Salisbury, M.; Burke, M.; Ishii, T. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1989)
Abstract Serpentine forms seamounts which rise asdiapirs in the Mariana fore-arc of the western Pacific. These have been imaged by side-scan sonar and sampled by dredging, sub-mersible dives and most recently by drillingin Leg 125 of the Ocean Drilling Program.The crust beneath the world's ocean basins is not dominated by serpentinite, so where do these serpentine seamounts come from? And where is this serpentine's water from? Water is incorporated into ocean crust inhydrous minerals like the serpentines and insediments on the mid-ocean ridges, and then travels with the spreading sea floor tosubduction zones, like the Mariana and Bonin Arcs. The water is released as sediment is squeezed and as hydrous minerals are heated in the down-going slab, and sometimes rises to serpentinize the ultra-mafic rocks of the overlying mantle wedge,so that serpentinite diapirs form which riseto the sea floor above. H.H. Hess once proposed that Layer 3 of the ocean crust was serpentinized mantle — serpentinized at mid-ocean ridges when water from inside the earth hydrated olivines and pyroxenesas the temperature cooled below 500°Cnear the sea floor. This hypothesis didn't stand up to subsequent tests, but Hess'proposal does seem to work in different circumstances in some island arc settings Andso, for example, we ask here if serpentinite-rich sediments are the products of ancient seamounts in Appalachian ophiolites? Serpentine doesn't merely affect islandarcs, ocean floors and ophiolites — it is mined as asbestos. And so in the mines ofthe Eastern Townships of Quebec serpentine unwittingly set the scene for the meeting of Jean Marchand, Gérard Pelletier and Pierre Elliott Trudeau in the great asbestos strike of 1949 — "La Grève des Amiantes",an usher, a prelude a political revolution, Quebec's Quiet Revolution.